The neurokinin-1 receptor antagonist aprepitant ameliorates oxidized LDL-induced endothelial dysfunction via KLF2. (February 2019) - Zheng, Jianghua; Chen, Kai; Zhu, Yanbin; Wang, Haifei; Chen, Zhilong; Yong, Xi; Yin, Hongshun; Chen, Jingquan; Lai, Kun; Liu, Yujuan
Highlights: NK-1R is expressed in HAECs and HUVECs and upregulated in response to ox-LDL. Aprepitant inhibits attachment of monocytes to HAECs by reducing vcam-1, E-selectin. Aprepitant promotes KLF-2/eNOS/NO signaling by activating ERK5. Effects of Aprepitant on cell adhesion, vcam-1, and E-selectin are dependent on KLF2. Abstract: Atherosclerosis is the main cause of many cardiovascular diseases. Endothelial dysfunction is recognized as an early event in the development of atherosclerosis. Many drugs have been studied to mitigate hyperlipidemia-induced endothelial injury. Studies have demonstrated that neuropeptide substance P (SP) and its preferred receptor neurokinin receptor 1 (NK-1R) are involved in the pathological progression of cardiovascular disease. In this study, we show that aprepitant, a selective NK-1R antagonist, possesses beneficial effects that protect endothelial cells from oxidized low-density lipoprotein (ox-LDL)-induced inflammatory response and injury. Our data demonstrate that NK-1R is expressed in both aortic and vein-originated endothelial cells and that ox-LDL treatment induces NK-1R expression. Treatment with aprepitant suppresses induction of endothelial vascular adhesion molecule (VCAM-1 and E-selectin) and cytokine by ox-LDL. The presence of aprepitant mitigates adhesion of monocytes to endothelial cells and the reduction in eNOS/NO triggered by ox-LDL. Mechanistically, we demonstrate that aprepitant suppresses ERK5-KLF2 axis activation. Silencing of KLF2 abolishes the inhibitory role of aprepitant on ox-LDL-induced inflammatory response, suggesting that its action is dependent on KLF2. Collectively, our data support that aprepitant exerts an anti-inflammatory effect. Further research is required to investigate the therapeutic potential of aprepitant in vascular inflammation resulting from atherosclerosis.